Monocytes from Chronic HBV Patients React In Vitro to HBsAg and TLR by Producing Cytokines Irrespective of Stage of Disease - Boltjes, Arjan (Public Library of Science, 2014)
Individuals who are chronically infected with the hepatitis B virus (HBV) are highly heterogenous with respect to serum levels of HBV DNA, HBV particles and viral proteins. Since circulating leukocytes, such as monocytes, are constantly exposed to these viral components, it is likely that the functionality of these cells is affected. However, at present, little information is available on the consequences of the interaction between monocytes and viral components. Therefore, we examined the in vitro effects of HBV surface antigen (HBsAg) on monocytes and evaluated whether these effects were reflected in vivo. We observed that in vitro HBsAg exposure of monocytes induced robust production of IL-6 and TNF. However, between chronic HBV patients with distinct levels of serum HBsAg, HBV early antigen (HBeAg), and HBV DNA, TLR-induced monocyte cytokine production did not differ. Importantly, HBsAg-induced cytokine production by monocytes was similar between patients and healthy controls showing that earlier in vivo exposure to HBsAg does not affect the in vitro response. Additionally, we show that IL-10 is able to inhibit cytokine production by HBsAg-induced monocytes. In conclusion, we demonstrate that monocytes can recognize and respond to HBsAg, resulting in vigorous pro-inflammatory cytokine production in vitro. However, phenotype and function of the monocyte compartment in chronic HBV patients are not influenced by differences in levels of serum viral components, suggesting that regulatory mechanisms are active to avoid excessive in vivo monocyte activation.